1996
DOI: 10.1002/j.1550-8528.1996.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss During 12 Weeks' Ad Libitum Carbohydrate‐Rich Diet in Overweight and Normal‐Weight Subjects at a Danish Work Site

Abstract: SIGGAARD, REGITZE, ANNE RABEN AND ARNE ASTRUP. Weight loss during 12 weeks' ad libitum carbohydrate-rich diet in overweight and normal-weight subjects at a Danish work site. Obes Res. 1996;4:347-356. The effect of 12 weeks' ad libitum carbohydrate-rich, low-fat diet on total body weight, lean body mass, and fat mass was studied in a group of healthy subjects at a Danish work-site (I) (n=50, BMI = 28.4 ± 0.7 kglm 2). Sixteen sublects served as controls (C) (BMI = 27.0 ± 1.0 kglm ). After 12 weeks the I subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…In contrast to individuals on a very low caloric diet, subjects consuming an ad libitum low-fat diet generally experience a reduction in fat mass without increased hunger. [34][35][36] In accordance with this, we could demonstrate in a previous study that the amount of reduction of overweight achieved with our treatment protocol was stable for at least 2-y. 22 Since circulating ghrelin levels are decreased not only in acute states of positive energy balance (caloric intake) but also in chronic states of positive energy balance (obesity), 1,10 this fact seems to conflict with our finding of relative stable ghrelin levels in reduction of overweight.…”
Section: Ghrelin In Obese Children T Reinehr Et Alsupporting
confidence: 89%
“…In contrast to individuals on a very low caloric diet, subjects consuming an ad libitum low-fat diet generally experience a reduction in fat mass without increased hunger. [34][35][36] In accordance with this, we could demonstrate in a previous study that the amount of reduction of overweight achieved with our treatment protocol was stable for at least 2-y. 22 Since circulating ghrelin levels are decreased not only in acute states of positive energy balance (caloric intake) but also in chronic states of positive energy balance (obesity), 1,10 this fact seems to conflict with our finding of relative stable ghrelin levels in reduction of overweight.…”
Section: Ghrelin In Obese Children T Reinehr Et Alsupporting
confidence: 89%
“…These results support the theory that macronutrient composition is of importance in addition to total energy intake consumed daily. 10,13,31,34 This result agrees with the general ®nding that high-fat diets result in obesity. 6,35 The fact that supplementation of CHO, as performed in this study, is not effective for weight maintenance, but overall increased CHOintake and lowered fat-intake is related to less BWregain, seems to suggest that supplementation of one food element is not the solution for maintenance of a stable BW.…”
Section: Weight Maintenance and Macronutrient Intakesupporting
confidence: 87%
“…Studies where fat is replaced with CHO, have been carried out to manipulate fat balance. Ad libitum food intake studies, in which CHO has provided an energy percentage of 55%, 10,31,32 have shown positive outcomes for weight maintenance and weight loss. The theory of Mean and standard deviations are presented.…”
Section: Weight Maintenance and Macronutrient Intakementioning
confidence: 99%
“…When expressed as percentage of initial body weight, the overall program resulted in a decrease of about 14% and lo%, which is comparable or even greater than the weight loss achieved in protocols that only used energy restricted diets (32,33), pharmacotherapy (34)(35)(36)(37)(38), and long-term change in diet composition (39). Despite this substantial impact of the program on body weight and composition of subjects, they experienced a resistance to lose fat at a time when their adiposity remained much higher than that of their lean controls.…”
Section: Discussionmentioning
confidence: 84%